Exports and Information Spillovers - Nicita, Alessandro (World Bank, Washington, DC, 2014)
Exporters' performance in a particular market may affect their future exports to the rest of the world. Importers may base their future transaction decision on the information revealed by exporters' past performance in other countries. Similarly, exporters acquire valuable information on foreign consumer tastes, product standards, or customs administration that may profitably be used in future transactions with other countries. the authors estimate the effects of these information spillovers across markets on the export patterns of four developing countries (Egypt, the Republic of Korea, Malaysia, and Tunisia). A dollar increase in exports to the United States generates on average an extra 2 to 14 cents of exports to the rest of the world in the next period. Social and ethnic networks seem to reinforce these information spillovers, especially in developing countries, where they appear to be geographically more concentrated. The exception is China and to some extent Hong Kong, probably reflecting a geographically more diversified migration pattern. The exchange of information among current and potentialexport markets can significantly affect a developing country's export performance. Bilateral information spillovers across markets are negligible or nonexistantfor exports from the United States, where there is less need to create a reputation in international markets. Similarly, Egypt's good export performancewould be more easily noticed in Argentina or India (where the market is small) than would increased exports to France or the United States.